Biomass hard carbon negative electrode material and preparation method and application thereof
By using soybean rhizobium to achieve nitrogen doping, the problems of uneven nitrogen doping and poor electrochemical performance of existing materials are solved, and efficient, uniform nitrogen doping and excellent electrochemical performance are achieved, with simple process and environmental protection.
Patent Information
- Application Number
- CN202510001284.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-02
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-01-02
AI Technical Summary
In commercial applications, existing hard carbon anode materials have problems such as uneven nitrogen doping, low first-time Coulomb efficiency, poor rate performance, poor cycle stability, and complex process, high energy consumption and high pollution.
Soybean rhizobium is used as a biomass precursor, and uniform doping of nitrogen elements is achieved through biological culture technology, and oxygen-containing functional groups are introduced in combination with pre-carbonization process, impurities and metal elements are removed through pickling treatment, simplifying the process, reducing energy consumption, and improving the electrochemical performance of the material.
It achieves uniform nitrogen doping, improves the first-time Coulomb efficiency, cycle stability and rate performance of the material. It has a simple process, low energy consumption, environmental protection, and is suitable for industrial production.
Smart Images

Figure CN119797323A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of negative electrode material preparation, and in particular to a biomass hard carbon negative electrode material and a preparation method and application thereof. Background Art
[0002] With the rapid development of science and technology in contemporary society, the demand for electrochemical energy storage devices represented by lithium-ion batteries is growing. However, the scarcity of lithium resources on the earth has led to large price fluctuations, while sodium is the fourth most abundant element in the earth's crust and has a wide distribution range. It is not restricted by resources and regions at all. At the same time, sodium-ion batteries have better safety performance and a service life comparable to that of lithium-ion batteries, so their application prospects are very broad. Positive and negative electrode materials are the core of the work of sodium-ion batteries. The two are not only the key to improving the performance of sodium-ion batteries, but also the main way to solve the cost bottleneck problem of sodium-ion batteries. Common negative electrode materials for sodium-ion batteries are alloy, conversion and embedded materials. Compared with alloy and conversion materials, embedded materials have Na during the charge and discharge process. + The lattice volume expansion rate during insertion and extraction is small, showing good structural integrity and cycle stability, and has higher first coulombic efficiency and higher rate performance. As a representative of embedded materials, carbon-based materials are regarded as the most promising negative electrode materials for sodium ion batteries due to their abundant resources and environmental friendliness.
[0003] Carbon-based materials are divided into four categories according to the stacking method of carbon atoms: graphite, graphene, soft carbon, and hard carbon. Hard carbon negative electrode materials have low sodium storage potential, high specific capacity, and wide sources, and are the focus of research on negative electrode materials for sodium ion batteries. Researchers have developed a series of hard carbon negative electrode materials based on asphalt-based, biomass-based, resin-based and other carbon-containing raw materials. Biomass genes have attracted much attention due to their unique advantages. For example, the raw material sources are abundant, easier to obtain, the carbon yield is high, it is environmentally friendly and contains a variety of elements. It is expected to become an ideal precursor for negative electrode materials for sodium ion batteries.
[0004] However, hard carbon negative electrode materials still face problems such as low first coulomb efficiency, poor rate performance, and poor cycle stability when they are commercially applied. In response to these problems, researchers have adopted some solutions, including adjustment of interlayer spacing, element doping, and optimization of pore structure. For example, CN202110783054.X discloses a nitrogen-doped hard carbon negative electrode material and its preparation method and application. A nitrogen-doped hard carbon negative electrode material with porous characteristics is obtained through primary purification, secondary purification, calcination, plasma treatment and other processes. The biomass raw materials include grapefruit peel, durian shell, coconut shell, almond, corn cob, shrimp shell, onion, soybean, mushroom, orchid leaf. The obtained hard carbon negative electrode material has the characteristics of large interlayer spacing, high porosity, and large specific surface area. However, its first coulomb efficiency is not high, and the excessive specific surface area is not conducive to the formation of a high-quality solid electrolyte interface film (SEI). The morphological uniformity of the hard carbon negative electrode material is also poor, and the process is complicated. It requires high-energy consumption and high-pollution ammonia plasma treatment, which may cause pollution to the atmosphere.
[0005] In summary, it is crucial to develop a fast, efficient and uniformly nitrogen-doped hard carbon negative electrode material and its preparation method, so that the material has a uniform surface morphology, high capacity, high initial efficiency, and long cycle life, and its preparation method is environmentally friendly and low in energy consumption. Summary of the invention
[0006] In view of the above-mentioned deficiencies in the prior art, the purpose of the present invention is to provide a biomass hard carbon negative electrode material and a preparation method and application thereof, aiming to solve the problems of uneven nitrogen doping, low first coulombic efficiency, poor uniformity of material surface morphology, complex process, high energy consumption and high pollution in the current hard carbon negative electrode materials.
[0007] To achieve the above object, the present invention adopts the following technical solution:
[0008] The first object of the present invention is to provide a biomass hard carbon negative electrode material, wherein the biomass precursor of the biomass hard carbon negative electrode material is soybean rhizobium. By adopting the technical solution, soybean rhizobium can fix the surrounding free nitrogen through nitrogen fixation, thereby achieving uniform and stable nitrogen doping, and obtaining a biomass hard carbon negative electrode material with uniform nitrogen doping, good morphology uniformity and high initial efficiency.
[0009] The second object of the present invention is to provide a method for preparing the above-mentioned biomass hard carbon negative electrode material, which utilizes biological culture technology to achieve uniform doping of nitrogen elements, combines a pre-carbonization process to introduce more oxygen-containing functional groups, and removes impure metal elements through acid washing. The preparation method is simple in process, low in cost, and the treatment process is environmentally friendly and conducive to industrial production. The preparation method comprises the following steps:
[0010] (1) Cultivating and growing soybean rhizobia in a culture medium;
[0011] (2) washing, drying, and crushing the soybean rhizobium obtained in step (1) to obtain soybean rhizobium powder;
[0012] (3) pre-carbonizing the soybean rhizobium powder obtained in step (2), taking it out after the pre-carbonization, cleaning it with a solvent and drying it, and then performing high-temperature carbonization and crushing to obtain a black powder product;
[0013] (4) The black powder product obtained in step (3) is subjected to acid leaching treatment to remove soluble metal elements such as potassium, calcium, magnesium, etc. in the material, and then post-processed to obtain a biomass hard carbon negative electrode material.
[0014] Preferably, in the step (1), the soybean rhizobium culture medium is yeast mannitol agar (YMA), and the YMA liquid culture medium is composed of (1 L): 10.0 g mannitol, 0.2-0.8 g yeast powder (as a nitrogen source), 0.4 g K2HPO4, 0.2 g MgSO4·7H2O, 0.1 g CaCl2·H2O, 0.1 g NaCl, 4 mL Rh trace element solution, and ddH2O is used to make the volume to 1 L. By using the culture medium, yeast extract is used as an amino acid source, contains B group vitamins and rhizobium growth factor, and can promote the growth of rhizobia.
[0015] Preferably, in step (1), the shaking speed is 150-250 r / min and the constant temperature is 28° C. By adopting the above temperature, the growth rate of soybean rhizobia can be the fastest.
[0016] Preferably, in step (1), the colony size of soybean rhizobia is not less than 1 cm.
[0017] Preferably, in step (2), the cultured rhizobia are first separated into solid and liquid using a centrifuge, and the separated solid is placed in an analytical grade formaldehyde solution and mechanically stirred to remove residual culture medium, wherein the mass ratio of the formaldehyde solution to the solid is 1:2 to 1:6, and the mixture is stirred thoroughly and then centrifuged, followed by filtration and cleaning with ethanol or isopropanol solution, and the solid is separated and then dried, the drying temperature is 60 to 100°C, and the drying time is 6 to 24 hours.
[0018] Furthermore, the centrifuge speed is 5000-8000 r / min, the centrifugal time is 2-5 min, the mixer speed is 150-500 r / min, and the stirring time is 0.5-2 h.
[0019] Preferably, in step (2), the soybean rhizobium is crushed by a wall breaking machine, and more preferably, the crushed product can pass through a 200-mesh sieve, i.e., the particle size is less than 0.074 mm.
[0020] Preferably, in step (3), the pre-carbonization treatment is specifically a hydrothermal method, the hydrothermal treatment time is 6 to 20 hours, the temperature is 150 to 400°C, and the mass volume ratio of the material to the liquid (the mass of the solid material and the volume of the liquid) is 1:2 to 1:4. By adopting the hydrothermal treatment, more oxygen elements can be introduced while making the material have a lower pore size (about 2 to 6 nm), further improving its initial efficiency.
[0021] Preferably, in step (3), the solid product after pre-carbonization is taken out for washing, and the washing solvent is one or more of water and alcohol solvents, and more preferably the alcohol solvent is at least one of ethanol and isopropanol.
[0022] Preferably, in step (3), the drying temperature is 60 to 100° C. and the drying time is 6 to 24 hours.
[0023] Preferably, in step (3), the high temperature carbonization treatment is specifically tubular furnace sintering, the heating rate is 5-10°C / min, the constant temperature is 700-1500°C, the constant temperature carbonization time is 4-10h, and the high temperature carbonization atmosphere is an inert atmosphere, more preferably at least one of argon and helium.
[0024] Preferably, in step (3), the crushing treatment is performed by ball milling, the ball milling speed is 300 to 800 r / min, the ball milling time is 0.5 to 4 h, and uniform particles with a particle size of 0.5 to 15 μm are obtained.
[0025] Preferably, in step (4), the acid leaching treatment is performed by immersing and stirring in a 1-5 mol / L hydrochloric acid solution for 1-5 hours at a stirring speed of 150-500 r / min.
[0026] Preferably, in step (4), the post-treatment includes: filtering the soaked solution to separate the solid powder, washing it with deionized water, and drying it to obtain the biomass hard carbon negative electrode material. More preferably, the drying treatment temperature is 60 to 100°C and the drying time is 6 to 24 hours.
[0027] The third object of the present invention is to provide an application of a biomass hard carbon negative electrode material in a sodium ion battery. When the biomass hard carbon negative electrode material is used as a negative electrode active material as a negative electrode of a sodium ion battery, it has the characteristics of high specific capacity, high first coulombic efficiency, and stable cycle.
[0028] Based on the above technical solution, the present invention has the following beneficial effects:
[0029] (1) In the present invention, yeast powder is added to the culture medium of soybean rhizobium as a nitrogen source, so that the nitrogen content of soybean rhizobium is increased and evenly distributed.
[0030] (2) In the present invention, the pre-carbonization process can introduce more oxygen-containing functional groups while fixing the carbon skeleton, that is, while maintaining a good surface morphology, more Na can be provided due to more oxygen-containing functional groups. + Adsorption sites can significantly improve the specific capacity of hard carbon materials.
[0031] (3) In the present invention, the pickling process can effectively remove soluble impurity metal elements such as potassium, calcium, magnesium, etc. in the hard carbon negative electrode material.
[0032] (4) The present invention adopts biomass precursors to prepare biomass hard carbon materials, which can achieve uniform nitrogen doping and further improve the electrochemical properties of the materials by regulating the preparation process conditions, thus having broad market application prospects. At the same time, the preparation method of the present invention is simple and suitable for large-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 The first cycle charge and discharge curve of the sodium ion battery assembled with the hard carbon negative electrode material prepared in Comparative Example 1;
[0034] Figure 2 The constant current cycle curve of the sodium ion battery assembled with the hard carbon negative electrode material prepared in Comparative Example 1;
[0035] Figure 3 This is the XPS spectrum of the hard carbon negative electrode material C1s prepared in Comparative Example 1;
[0036] Figure 4 The first cycle charge and discharge curve of the sodium ion battery assembled with the hard carbon negative electrode material prepared in Example 1;
[0037] Figure 5 The constant current cycle curve of the sodium ion battery assembled with the hard carbon negative electrode material prepared in Example 1;
[0038] Figure 6 This is the XPS spectrum of the hard carbon negative electrode material C1s prepared in Example 1.
[0039] Figure 7 This is the SEM image of the hard carbon negative electrode material prepared in Example 1.
[0040] Figure 8 It is a comparison chart of the rate performance of Example 1, Example 3, Comparative Example 1 and Comparative Example 2.
[0041] Fig. 9 This is the isothermal adsorption-desorption curve of Example 1. DETAILED DESCRIPTION
[0042] The invention provides a biomass hard carbon negative electrode material and its preparation method and application. In order to better clarify and understand the purpose, process scheme and advantages of the present invention, the technical scheme and implementation method of the present invention are further described clearly, completely and in detail through specific examples and in combination with the accompanying drawings. It should be known that the embodiments described in the present invention are implemented on the premise of the technical scheme of the present invention, and detailed implementation methods and specific operating processes are given, but they are only part of the embodiments of the present invention, not all of the embodiments. The specific implementation methods described are limited to explaining and interpreting the present invention, and do not limit the present invention. Based on the embodiments in the present invention, all other implementation methods obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0043] The experimental methods and conditions used in the embodiments of the present invention are conventional methods and conventional conditions unless otherwise specified. The materials, reagents or instruments used in the embodiments, unless otherwise specified, can be obtained from commercial sources or prepared by conventional methods. The reaction conditions embodied in the content of the invention of the present invention can achieve the reaction and obtain the product of the expected effect. Due to space limitations, some embodiments are listed below to further illustrate the advantages of the technical solution of the present invention.
[0044] Embodiment 1:
[0045] A biomass hard carbon negative electrode material and its specific preparation steps are as follows:
[0046] (1) Yeast mannitol agar (YMA) liquid medium composition (1 L): 10.0 g mannitol, 0.8 g yeast powder (as nitrogen source), 0.4 g K2HPO4, 0.2 g MgSO4·7H2O, 0.1 g CaCl2·H2O, 0.1 g NaCl, 4 mL Rh trace element solution, fixed to 1 L with ddH2O. Soybean rhizobia were inoculated into YMA medium and cultured in a shaking incubator at 170 r / min and 28°C for 48 h.
[0047] (2) Separate the cultured rhizobia from the solid and liquid using a centrifuge at a speed of 5000 r / min for 5 minutes. Use analytically pure formaldehyde solution to mechanically stir the separated solid at a speed of 150 r / min for 2 hours. The mass volume ratio of formaldehyde solution to solid is 1:4. After sufficient stirring, centrifuge at a speed of 5000 r / min for 2 minutes. After centrifugation, use ethanol to filter and wash. After separating the solid, place it in an oven for drying at a temperature of 60°C for 24 hours. After drying, use a wall breaker to crush it into powder for 3 minutes.
[0048] (3) Place the powder in a hydrothermal reactor, the solvent is deionized water, and the mass-to-volume ratio of the feed to the liquid is 1:2. Place the reactor in a hydrothermal oven, the hydrothermal temperature is 180°C, and the hydrothermal time is 12 hours. After the hydrothermal reaction is completed, take it out, filter it, and separate the solid. Place the separated solid in anhydrous ethanol, stir it manually and continue to filter it, repeat 3 times. Place the final solid in a 60°C oven and bake it for 24 hours to obtain a fluffy powder. Place the powder in a porcelain boat, shake it flat, and place it in a tubular furnace. In an argon environment, the heating rate is 5°C / min, the insulation temperature is 700°C, and the insulation time is 10 hours. Place the obtained product in a ball mill for crushing, the ball mill speed is 800r / min, and the ball mill time is 0.5h.
[0049] (4) The crushed powder was placed in a 1 mol / L hydrochloric acid solution and stirred for 5 h at a stirring speed of 150 r / min. The stirred solution was filtered to separate the solid and washed with deionized water until the pH value was 7. The washed solid was placed in an oven at 60°C and dried for 24 h to obtain a hard carbon negative electrode material.
[0050] The obtained hard carbon negative electrode material, conductive carbon black and binder PVDF were mixed evenly in a mass ratio of 8:1:1, and then an appropriate amount of NMP was added as a solvent and stirred evenly; the above slurry was evenly coated on an aluminum sheet with a thickness of 150 mm; then, the electrode was placed in a vacuum oven at 80°C and dried for 8 hours and then compacted to make a negative electrode; CR2303 button batteries were assembled in an argon-filled glove box, with glass fiber Whatman GF / D as the diaphragm, 1 mol / L NaPF6 DEC:EC:PC=1:1:1 as the electrolyte, and a metal sodium sheet as the reference electrode.
[0051] The assembled button cell was tested at 30°C, with a current density of 0.03A / g in the first three cycles and a current density of 0.2A / g in the subsequent cycles. Figure 4 As shown, the battery's first coulombic efficiency is 86%. Figure 5 As shown in Figure 2, the specific capacity after 200 cycles is 176 mA h / g. The XPS spectrum of C1 s is shown in Figure 2. Figure 6 As shown, the ratios of CO / CN and C=O functional groups are 22.4% and 24.5%, respectively.
[0052] Embodiment 2:
[0053] A biomass hard carbon negative electrode material and its specific preparation steps are as follows:
[0054] (1) Yeast mannitol agar (YMA) liquid medium composition (1 L): 10.0 g mannitol, 0.6 g yeast powder (as nitrogen source), 0.4 g K2HPO4, 0.2 g MgSO4·7H2O, 0.1 g CaCl2·H2O, 0.1 g NaCl, 4 mL Rh trace element solution, fixed to 1 L with ddH2O. Soybean rhizobia were inoculated into YMA medium and cultured in a shaking incubator at 150 r / min and 28°C for 36 h.
[0055] (2) Separate the cultured rhizobia from the solid and liquid using a centrifuge at a speed of 5000 r / min for 5 minutes. Use analytically pure formaldehyde solution to mechanically stir the separated solid at a speed of 200 r / min for 1 hour. The mass volume ratio of formaldehyde solution to solid is 1:2. After sufficient stirring, centrifuge at a speed of 5000 r / min for 5 minutes. After centrifugation, use isopropanol to filter and wash. After separating the solid, place it in an oven for drying at a temperature of 100°C for 6 hours. After drying, use a wall breaker to crush it into powder for 3 minutes.
[0056] (3) The powder is placed in a hydrothermal reactor, the solvent is deionized water, and the mass volume ratio of the feed to the liquid is 1:4. The reactor is placed in a hydrothermal oven, the hydrothermal temperature is 400°C, and the hydrothermal time is 6 hours. After the hydrothermal reaction is completed, take it out, filter it, and separate the solid. The separated solid is placed in anhydrous ethanol, manually stirred evenly, and then filtered, and repeated 3 times. The final solid is placed in a 100°C oven and baked for 6 hours to obtain a fluffy powder. The powder is placed in a porcelain boat, shaken flat, and placed in a tubular furnace. The heating rate is 5°C / min under an argon environment, the insulation temperature is 1100°C, and the insulation time is 6 hours. The obtained product is placed in a ball mill for crushing, the ball mill speed is 500r / min, and the ball mill time is 1 hour.
[0057] (4) The crushed powder was placed in a 2 mol / L hydrochloric acid solution and stirred for 1 h at a stirring speed of 300 r / min. The stirred solution was filtered to separate the solid and washed with deionized water until the pH was 7. The washed solid was placed in an oven at 80°C and dried for 12 h to obtain a hard carbon negative electrode material.
[0058] The obtained hard carbon negative electrode material was assembled into a battery according to the method of Example 1.
[0059] The assembled button cell was tested at 30°C, with a current density of 0.03A / g in the first three cycles and a current density of 0.2A / g in the subsequent cycles. The specific capacity after 200 cycles was 134mA h / g, and the first coulombic efficiency was 70%.
[0060] Embodiment 3:
[0061] A biomass hard carbon negative electrode material and its specific preparation steps are as follows:
[0062] (1) Yeast mannitol agar (YMA) liquid medium composition (1 L): 10.0 g mannitol, 0.6 g yeast powder (as nitrogen source), 0.4 g K2HPO4, 0.2 g MgSO4·7H2O, 0.1 g CaCl2·H2O, 0.1 g NaCl, 4 mL Rh trace element solution, fixed to 1 L with ddH2O. Soybean rhizobia were inoculated into YMA medium and cultured in a shaking incubator at 170 r / min and 28°C for 36 h.
[0063] (2) Separate the cultured rhizobia from the solid and liquid using a centrifuge at a speed of 8000 r / min for 2 min. Use analytically pure formaldehyde solution to mechanically stir the separated solid at a speed of 500 r / min for 0.5 h. The mass volume ratio of formaldehyde solution to solid is 1:4. After sufficient stirring, centrifuge at a speed of 5000 r / min for 2 min. After centrifugation, use ethanol to filter and wash. After separating the solid, place it in an oven for drying at a temperature of 60 ° C for 24 h. After drying, use a wall breaker to crush it into powder for 3 min.
[0064] (3) The powder is placed in a hydrothermal reactor, the solvent is deionized water, and the mass-to-volume ratio of the feed to the liquid is 1:2. The reactor is placed in a hydrothermal oven, the hydrothermal temperature is 150°C, and the hydrothermal time is 20 hours. After the hydrothermal reaction is completed, take it out, filter it, and separate the solid. The separated solid is placed in anhydrous ethanol, manually stirred evenly, and then filtered, and repeated 3 times. The final solid is placed in a 100°C oven and baked for 6 hours to obtain a fluffy powder. The powder is placed in a porcelain boat, shaken flat, and placed in a tubular furnace. The heating rate is 5°C / min under an argon environment, the insulation temperature is 1500°C, and the insulation time is 4 hours. The obtained product is placed in a ball mill for crushing, the ball mill speed is 500r / min, and the ball mill time is 1 hour.
[0066] (4) The crushed powder was placed in a 5 mol / L hydrochloric acid solution and stirred for 1 h at a stirring speed of 500 r / min. The stirred solution was filtered to separate the solid and washed with deionized water until the pH was 7. The washed solid was placed in an oven at 100°C and dried for 6 h to obtain a hard carbon negative electrode material.
[0067] The obtained hard carbon negative electrode material was assembled into a battery according to the method of Example 1.
[0068] The assembled button cell was tested at 30°C, with a current density of 0.03A / g in the first three cycles and a current density of 0.2A / g in the subsequent cycles. The specific capacity after 200 cycles was 153mA h / g, and the first coulombic efficiency was 76%.
[0069] Comparative Example 1:
[0070] A biomass hard carbon negative electrode material and its specific preparation steps are as follows:
[0071] (1) Yeast mannitol agar (YMA) liquid medium composition (1 L): 10.0 g mannitol, 0.2 g yeast powder (as nitrogen source), 0.4 g K2HPO4, 0.2 g MgSO4·7H2O, 0.1 g CaCl2·H2O, 0.1 g NaCl, 4 mL Rh trace element solution, and ddH2O was used to make up to 1 L. Soybean rhizobia were inoculated into YMA medium and cultured in a shaking incubator at 250 r / min and 28°C for 36 h.
[0072] (2) Separate the cultured rhizobia from the solid and liquid using a centrifuge at a speed of 5000 r / min for 5 minutes. Use analytically pure formaldehyde solution to mechanically stir the separated solid at a speed of 150 r / min for 2 hours. The mass volume ratio of formaldehyde solution to solid is 1:4. After sufficient stirring, centrifuge at a speed of 5000 r / min for 5 minutes. After centrifugation, use ethanol to filter and wash. After separating the solid, place it in an oven for drying at a temperature of 60°C for 24 hours. After drying, use a wall breaker to crush it into powder for 3 minutes.
[0073] (3) The powder was placed in a hydrothermal reactor, the solvent was deionized water, and the mass volume ratio of the feed to the liquid was 1:2. The reactor was placed in a hydrothermal oven, the hydrothermal temperature was 180°C, and the hydrothermal time was 12 hours. After the hydrothermal reaction was completed, it was taken out, filtered, and the solid was separated. The separated solid was placed in anhydrous ethanol, manually stirred evenly, and then filtered, and repeated 3 times. The final solid was placed in a 60°C oven and dried for 24 hours to obtain a fluffy powder. The powder was placed in a porcelain boat, shaken flat, placed in a tubular furnace, and an argon atmosphere was introduced. The heating rate was 5°C / min, the insulation temperature was 700°C, and the insulation time was 10 hours. The obtained product was placed in a ball mill for crushing, the ball mill speed was 300r / min, and the ball mill time was 4 hours.
[0074] (4) The crushed powder was placed in a 1 mol / L hydrochloric acid solution and stirred for 5 h at a stirring speed of 150 r / min. The stirred solution was filtered to separate the solid and washed with deionized water until the pH was 7. The washed solid was placed in a 60°C oven and dried for 12 h to obtain a hard carbon negative electrode material.
[0075] The obtained hard carbon negative electrode material was assembled into a battery according to the method of Example 1.
[0076] The assembled button cell was tested at 30°C, with a current density of 0.03A / g in the first three cycles and a current density of 0.2A / g in the subsequent cycles. Figure 1 As shown, the battery's first coulombic efficiency is 63%. Figure 2 As shown in Figure 2, the specific capacity after 200 cycles is 96 mA h / g. The XPS spectrum of C1 s is shown in Figure 2. Figure 3 As shown, the ratios of CO / CN and C=O functional groups are 14.5% and 20.4% respectively. Compared with Example 1, it can be seen that the electrochemical performance is significantly affected by changing the amount of yeast powder.
[0077] Comparative Example 2:
[0078] A biomass hard carbon negative electrode material and its specific preparation steps are as follows:
[0079] (1) Yeast mannitol agar (YMA) liquid medium composition (1 L): 10.0 g mannitol, 0.2 g yeast powder (as nitrogen source), 0.4 g K2HPO4, 0.2 g MgSO4·7H2O, 0.1 g CaCl2·H2O, 0.1 g NaCl, 4 mL Rh trace element solution, and ddH2O was used to make up to 1 L. Soybean rhizobia were inoculated into YMA medium and cultured in a shaking incubator at 170 r / min and 28°C for 36 h.
[0080] (2) Separate the cultured rhizobia from the solid and liquid using a centrifuge at a speed of 5000 r / min for 5 minutes. Use analytically pure formaldehyde solution to mechanically stir the separated solid at a speed of 150 r / min for 2 hours. The mass volume ratio of formaldehyde solution to solid is 1:4. After sufficient stirring, centrifuge at a speed of 5000 r / min for 2 minutes. After centrifugation, use ethanol to filter and wash. After separating the solid, place it in an oven for drying at a temperature of 60°C for 24 hours. After drying, use a wall breaker to crush it into powder for 3 minutes.
[0081] (3) The powder was placed in a porcelain boat, shaken flat, and placed in a tube furnace. Argon atmosphere was introduced, and the heating rate was 5°C / min. The holding temperature was 700°C and the holding time was 10h. The obtained product was placed in a ball mill for crushing. The ball mill speed was 800r / min and the ball milling time was 0.5h.
[0082] (4) The crushed powder was placed in a 1 mol / L hydrochloric acid solution and stirred for 5 h at a stirring speed of 150 r / min. The stirred solution was filtered to separate the solid and washed with deionized water until the pH was 7. The washed solid was placed in an oven at 70°C and dried for 18 h to obtain a hard carbon negative electrode material.
[0083] The obtained hard carbon negative electrode material was assembled into a battery according to the method of Example 1.
[0084] The assembled button cell was tested at 30°C, with a current density of 0.03A / g in the first three cycles and a current density of 0.2A / g in the subsequent cycles. The specific capacity after 200 cycles was 77mA h / g, and the first coulombic efficiency was 45%.
[0085] Comparative Example 3:
[0086] A biomass hard carbon negative electrode material and its specific preparation steps are as follows:
[0087] (1) Yeast mannitol agar (YMA) liquid medium composition (1 L): 10.0 g mannitol, 0.4 g K2HPO4, 0.2 g MgSO4·7H2O, 0.1 g CaCl2·H2O, 0.1 g NaCl, 4 mL Rh trace element solution, fixed to 1 L with ddH2O. Soybean rhizobia were inoculated into YMA medium and cultured in a shaking incubator at 170 r / min and 28°C for 36 h.
[0088] (2) Separate the cultured rhizobia from the solid and liquid using a centrifuge at a speed of 5000 r / min for 5 minutes. Use analytically pure formaldehyde solution to mechanically stir the separated solid at a speed of 150 r / min for 2 hours. The mass volume ratio of formaldehyde solution to solid is 1:4. After sufficient stirring, centrifuge at a speed of 5000 r / min for 2 minutes. After centrifugation, use ethanol to filter and wash. After separating the solid, place it in an oven for drying at a temperature of 60°C for 24 hours. After drying, use a wall breaker to crush it into powder for 3 minutes.
[0089] (3) The powder was placed in a porcelain boat, shaken flat, and placed in a tube furnace for air sintering at a heating rate of 5°C / min, a holding temperature of 400°C, and a holding time of 4 hours. Without waiting for the temperature to drop, argon gas was directly introduced at a heating rate of 5°C / min, a holding temperature of 700°C, and a holding time of 10 hours. The obtained product was placed in a ball mill for crushing at a ball mill speed of 800 r / min and a ball milling time of 0.5 hours.
[0090] (4) The crushed powder was placed in a 1 mol / L hydrochloric acid solution and stirred for 5 h at a stirring speed of 150 r / min. The stirred solution was filtered to separate the solid and washed with deionized water until the pH value was 7. The washed solid was placed in an oven at 60°C and dried for 6 h to obtain a hard carbon negative electrode material.
[0091] The obtained hard carbon negative electrode material was assembled into a battery according to the method of Example 1.
[0092] The assembled button cell was tested at 30°C, with a current density of 0.03A / g in the first three cycles and a current density of 0.2A / g in the subsequent cycles. The specific capacity after 200 cycles was 56mA h / g, and the first coulombic efficiency was 37%. Compared with the example, it can be seen that the electrochemical performance was significantly reduced due to the lack of yeast powder and the use of the wrong pretreatment method.
[0093] The specific surface area, average pore size and interlayer spacing of the materials obtained in Examples 1 to 3 and Comparative Examples 1 to 3 were tested, and the specific parameters are shown in Table 1.
[0094] Table 1 Summary of structural parameters of examples and comparative examples
[0095]
[0096] The batteries obtained in Examples 1 to 3 and Comparative Examples 1 to 3 were tested for the first coulombic efficiency and the 200th cycle discharge capacity, which further showed that the sodium ion battery using the hard carbon negative electrode sheet of the present application still maintained a relatively high charge and discharge capacity after cycling, as shown in Table 2 for details.
[0097] Table 2 Summary of electrochemical properties of examples and comparative examples
[0098]
[0099] The above-described embodiment is only a preferred solution of the present invention and does not limit the present invention in any form. There are other variations and modifications without exceeding the technical solution described in the claims.
Claims
1. A biomass hard carbon negative electrode material, characterized in that: The biomass precursor of the biomass hard carbon negative electrode material is soybean rhizobium.
2. A method for preparing the biomass hard carbon negative electrode material as claimed in claim 1, characterized in that: The steps include: (1) Cultivating and growing soybean rhizobia in a culture medium; (2) washing, drying, and crushing the soybean rhizobium to obtain soybean rhizobium powder; (3) pre-carbonizing the soybean rhizobium powder, and then performing high-temperature carbonization and crushing treatment; (4) The product is subjected to acid leaching treatment and then post-processed to obtain a biomass hard carbon negative electrode material.
3. The method for preparing a biomass hard carbon negative electrode material according to claim 2, characterized in that: The culture medium in step (1) is yeast mannitol agar.
4. The method for preparing a biomass hard carbon negative electrode material according to claim 3, characterized in that: The culture medium composition is: 10.0g mannitol, 0.2-0.8g yeast powder (as nitrogen source), 0.4g K2HPO4, 0.2g MgSO4·7H2O, 0.1g CaCl2·H2O, 0.1g NaCl, 4mL Rh trace element solution, and fixed to 1L with ddH2O.
5. The method for preparing a biomass hard carbon negative electrode material according to claim 2, characterized in that: In the step (2), the product is crushed and passed through a 200-mesh sieve.
6. The method for preparing a biomass hard carbon negative electrode material according to claim 2, characterized in that: In the step (3), the pre-carbonization treatment is a hydrothermal method, the hydrothermal treatment time is 6 to 20 hours, the temperature is 150 to 400° C., and the mass volume ratio of the feed to the liquid is 1:2 to 1:
4.
7. The method for preparing a biomass hard carbon negative electrode material according to claim 2, characterized in that: In the step (3), the heating rate of the high-temperature carbonization treatment is 5 to 10°C / min, the constant temperature is 700 to 1500°C, the carbonization time is 4 to 10 hours, and the high-temperature carbonization atmosphere is argon.
8. The method for preparing a biomass hard carbon negative electrode material according to claim 2, characterized in that: In the step (3), the crushing treatment is specifically a ball milling method, the ball milling speed is 300 to 800 r / min, and the ball milling time is 0.5 to 4 h.
9. The method for preparing a biomass hard carbon negative electrode material according to claim 2, characterized in that: In the step (4), the acid leaching treatment is performed by immersing and stirring the mixture in a 1 to 5 mol / L hydrochloric acid solution for 1 to 5 hours at a stirring speed of 150 to 500 r / min.
10. Use of the biomass hard carbon negative electrode material as claimed in claim 1 or prepared by the preparation method according to any one of claims 2 to 9 in a sodium ion battery.
Citation Information
Patent Citations
Nitrogen-doped hard carbon material and preparation method and application thereof
CN113493195A
Preparation method of bacterial cellulose based carbon nanofibers
CN103820883A
Fe3O4 / C composite material prepared by utilization of rice root and application thereof
CN103840152A
Biomass-derived nitrogen-doped hard carbon material as well as preparation method and application thereof
CN115285969A
Soybean rhizobium screening method and cultivation method
CN118745390A